20.3k views
4 votes
X + 3 ÷ 2 = 12 - 2 ÷ 2

1 Answer

7 votes

x=19/2

For this expression,

x + 3 ÷ 2 = 12 - 2 ÷ 2​

Let's use the PEMDA acronym

P Parentheses

E Exponents

M Multiplication

D Division

A Addition

2) Solving it, let's firstly rewrite that expression

And then subtract 3/2 from both sides.


\begin{gathered} x\text{ +3/2 = 12-2/2} \\ x=12-1-(3)/(2) \\ x=11\text{ -3/2} \\ x=(19)/(2) \end{gathered}

Proceeding the operations, we get 19/2

Testing it:

19/2 +3/2 = 12-2/2

11 =11 True

User Fernando Morales
by
5.4k points